Impacts of Organizational Responses on Customer Satisfaction and Loyalty in Northern Cyprus Hotels and Casinos - Fard, Samaneh Bahrololumi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Strategically, every organization follows a specific systematic plan of action to control the service recovery procedures, namely organizational responses. Organizational responses vary due to different approaches and opinions; however, six responses are usually referenced in the literature: timeliness, redress, facilitation, credibility, attentiveness and apology. Therefore, Investigation of the impacts of organizational responses on hotel-casino customers‟ satisfaction and loyalty in Northern Cyprus hotels and casinos provides useful information for policy makers and managers. Results show that while atonement, facilitation and attentiveness show statistically significant and positive relationships with customer satisfaction and loyalty, apology, promptness show different behaviors in Northern Cyprus hotels and casinos. In addition, it should be noted that creditability as an organizational response is measured but no significant result has shown up. Keywords: Organizational responses, Service Recovery, Customer Satisfaction, Customer Loyalty.

ÖZ: Stratejik olarak, her kuruluş kurtarma prosedürleri yani örgütsel tepkileri kontrol etmek için belli bir sistematik eylem planı takip eder. Örgütsel tepkiler farklı yaklaşımlar ve görüşler nedeniyle değişebilir, ancak, genellikle literatürde başvurulan altı metod: zamanındalık, telafi, kolaylaştırma, güvenilirlik, dikkat ve özür. Bu nedenle, Kuzey Kıbrıs oteller ve casinolar otel-casino müşteri memnuniyeti ve sadakati üzerindeki örgütsel tepkilerin etkilerinin incelenmesi hareket tarzını belirleyenler ve yöneticiler için yararlı bilgiler sağlar. Sonuçlar gösteriyor ki, telafi, kolaylaştırma ve dikkat bize istatistik olarak önemli müşteri memnuniyeti gösterirken sadakat, özür, dakiklik ise Kuzey Kıbrıs oteller ve casinolarında farklı davranışlar göstermektedir. Buna ek olarak, dikkate alınmalıdır ki beğeni örgütsel tepkiler olarak ölçülmekte ancak etkili bir sonuç olarak gösterilmemektedir. Anahtar Kelimeler: Örgütsel tepkiler , Servis Kurtarma , Müşteri Memnuniyeti , Müşteri Sadakati.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2014. Supervisor: Prof. Dr. Hasan Kılıç.
Keywords: Tourism; Organizational effectiveness; Organizational behavior; Customer Services - Hotel Industry - Cyprus, Northern; Consumer Satisfaction - Tourism - Cyprus, Northern; Organizational responses; Service Recovery; Customer Satisfaction; Customer Loyalty